2023
DOI: 10.3390/biology12081060
|View full text |Cite
|
Sign up to set email alerts
|

Biological and Genetic Characterizations of a Novel Lytic ΦFifi106 against Indigenous Erwinia amylovora and Evaluation of the Control of Fire Blight in Apple Plants

Abstract: Erwinia amylovora is a devastating phytobacterium causing fire blight in the Rosaceae family. In this study, ΦFifi106, isolated from pear orchard soil, was further purified and characterized, and its efficacy for the control of fire blight in apple plants was evaluated. Its genomic analysis revealed that it consisted of 84,405 bp and forty-six functional ORFs, without any genes encoding antibiotic resistance, virulence, and lysogenicity. The phage was classified into the genus Kolesnikvirus of the subfamily Ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…Finally, in this analysis, based on complete genomes, another noteworthy result was observed: the new E. amylovora phage isolates from Mediterranean settings show a significant similarity to other E. amylovora phages isolated in Belarus (OM522317), France (OQ818707), Switzerland [ 35 ], and South Korea [ 88 ]. This finding suggests that phage species within this clade, in addition to potentially being specific to E. amylovora , exhibit a low degree of genetic divergence, similar to what is observed in the pangenome of E. amylovora .…”
Section: Resultsmentioning
confidence: 83%
“…Finally, in this analysis, based on complete genomes, another noteworthy result was observed: the new E. amylovora phage isolates from Mediterranean settings show a significant similarity to other E. amylovora phages isolated in Belarus (OM522317), France (OQ818707), Switzerland [ 35 ], and South Korea [ 88 ]. This finding suggests that phage species within this clade, in addition to potentially being specific to E. amylovora , exhibit a low degree of genetic divergence, similar to what is observed in the pangenome of E. amylovora .…”
Section: Resultsmentioning
confidence: 83%
“…Jo et al [ 36 ] isolated the fire blight bacteriophage pEp_SNUABM_03, which showed tolerance to temperatures up to 40 °C and pH levels between 4 and 9. Choe et al [ 37 ] isolated the fire blight bacteriophage ΦFifi106, which maintained certain activity at temperatures up to 50 °C, pH levels between 4 and 11, and under 6 h of UV irradiation.…”
Section: Discussionmentioning
confidence: 99%
“…The "fire blight" bacteria attack buds and flowers, reducing significantly the production of pears and apples around the world. For this reason, E. amylovora has been classified as a quarantine organism in several countries [23,26,27].…”
Section: Introductionmentioning
confidence: 99%